Testicular Volumes Measurement Comparison by Ultrasound and Orchidometer and Its Relationship with Nutritional Status in Transfusion-dependent Thalassemia - Rahmad Mulyadi; Joedo Prihartono; Em Yunir; Dian Anindita Lubis; Reyhan Eddy Yunus (Indonesian Biomedical Journal, 2023)
BACKGROUND: One type of thalassemia known as transfusion-dependent thalassemia (TDT) requires a lifelong blood transfusion. Iron overload from prolonged blood transfusions causes nutritional disorders and several organs impairment, including the testicles. In contrast to an orchidometer, ultrasound shows more details of the testicles. This study aimed to compare testicular volumes based on ultrasound and orchidometer measurements and correlate testicular volume with nutritional status in TDT patients.